2022
DOI: 10.1177/10600280221101105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Opportunities for Oral Antibiotic Therapy in Bone and Joint Infections

Abstract: Background: The OVIVA trial suggests oral antibiotics are an alternative to intravenous antibiotics to treat bone and joint infections (BJI). A shift in practice to treatment with oral antibiotics would eliminate the need for central vascular access, improve patient satisfaction, and reduce overall healthcare costs. Objective: The primary objective was to identify the proportion of patients treated for BJIs with outpatient parenteral antimicrobial therapy (OPAT) who would have qualified for oral antibiotics ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The oral versus intravenous antibiotics for bone and joint infection (OVIVA) study found that oral antibiotic treatment was noninferior to IV treatment when used during the first 6 weeks in the management of bone and joint infections [ 11 ]. This suggested that earlier switching to oral agents may confer cost savings and reduced complications related to IV administration of medications [ 12 , 13 ]. However, the subgroup analysis in the OVIVA study shows that patients with retained metal had greater treatment failures while on oral agents when compared to intravenous agents, and in our study population 29.3% of subjects had DAIR as a surgical intervention and therefore had metal implant retention.…”
Section: Discussionmentioning
confidence: 99%
“…The oral versus intravenous antibiotics for bone and joint infection (OVIVA) study found that oral antibiotic treatment was noninferior to IV treatment when used during the first 6 weeks in the management of bone and joint infections [ 11 ]. This suggested that earlier switching to oral agents may confer cost savings and reduced complications related to IV administration of medications [ 12 , 13 ]. However, the subgroup analysis in the OVIVA study shows that patients with retained metal had greater treatment failures while on oral agents when compared to intravenous agents, and in our study population 29.3% of subjects had DAIR as a surgical intervention and therefore had metal implant retention.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are important because it remains common US practice to use intravenous beta-lactams or glycopeptides for definitive therapy of PJI due to staphylococci susceptible to oral antibiotics, and these data suggest that adding rifampin in such cases may be contributing toxicity (eg, hepatotoxicity, interactions with anticoagulation, antiplatelet agents, and opioid analgesia, and nausea) without benefit [ 8 ]. Our study adds to other work suggesting that the potential benefit of rifampin in staphylococcal PJI is restricted to specific clinical scenarios, such as knee vs hip PJI, and when rifampin is added later in the treatment course vs immediately after surgery [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FQ-rif regimen may be more poorly tolerated than alternatives. A modern retrospective cohort of staphylococcal PJI found a 35.6% unplanned drug discontinuation rate with fluoroquinolones vs 3% with other regimens, though notably another recent cohort study found a similarly high rate of unplanned change in antibiotics with standard intravenous antimicrobials [ 8 , 13 ]. In addition, a recent Veterans Affairs cohort with 4624 patients who received DAIR for PJI suggested a small overall benefit to adjunctive rifampin, albeit with no stratification of outcomes by use of a quinolone [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As others have noted, changing the standard of care from IV to oral antibiotics will likely lead to fewer adverse outcomes and reduced cost of care. 18 Focused efforts by antimicrobial stewardship programs to reduce outpatient IV vancomycin use through protocolization, provider education, and other means should be encouraged. 11…”
Section: General Malaisementioning
confidence: 99%
“…Given the higher prevalence of MRSA in the US compared to Europe, clinicians may be less willing to apply the results of the OVIVA trial to a US population. That said, a recent analysis estimated that using oral instead of IV antibiotics for patients with orthopedic infections would save over $3000/patient 18 . Clearly, if we can safely switch patients from IV to PO antibiotics for the treatment of orthopedic infections, we should do so to help overcome the above concerns of IV therapy.…”
Section: Introductionmentioning
confidence: 99%